Playing simple loony dots and boxes endgames optimally - Buzzard,K; Ciere,M (Integers: electronic journal of combinatorial number theory, 2014)
We explain a highly efficient algorithm for playing the simplest type of dotsand boxes endgame optimally (by which we mean "in such a way so as to maximisethe number of boxes that you take"). The algorithm is sufficiently simple thatit can be learnt and used in over-the-board games by humans. The types ofendgames we solve come up commonly in practice in well-played games on a 5x5board and were in fact developed by the authors in order to improve theirover-the-board play.